2017
DOI: 10.1088/0026-1394/54/1a/08007
|View full text |Cite
|
Sign up to set email alerts
|

Key comparison study on peptide purity—synthetic human C-peptide

Abstract: Under the auspices of the Protein Analysis Working Group (PAWG) of the Comité Consultatif pour la Quantité de Matière (CCQM) a key comparison, CCQM-K115, was coordinated by the Bureau International des Poids et Mesures (BIPM) and the Chinese National Institute of Metrology (NIM). Eight Metrology Institutes or Designated Institutes and the BIPM participated. Participants were required to assign the mass fraction of human C-peptide (hCP) present as the main component in the comparison sample for CCQM-K115. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The PAWG has decided in April 2016 to use the TFA mass fraction and corresponding combined uncertainty of 57.1 ± 1.9 mg/g obtained by the NIM by ion chromatography for the calculation of the key comparison reference value for the mass fraction of hCP. The TFA mass fraction value obtained by the NIM in CCQM-K115 has been confirmed by the NRC through qNMR in CCQM-P55.2 [20].…”
Section: / 28mentioning
confidence: 56%
See 3 more Smart Citations
“…The PAWG has decided in April 2016 to use the TFA mass fraction and corresponding combined uncertainty of 57.1 ± 1.9 mg/g obtained by the NIM by ion chromatography for the calculation of the key comparison reference value for the mass fraction of hCP. The TFA mass fraction value obtained by the NIM in CCQM-K115 has been confirmed by the NRC through qNMR in CCQM-P55.2 [20].…”
Section: / 28mentioning
confidence: 56%
“…Sorption balance measurements indicated that weighings of the CCQM-K115/P55.2 comparison material need to be performed under controlled conditions of temperature and relative humidity (RH) as the water content of the comparison material changes reversibly as a function of the RH. A full summary of the results for hCP mass fraction and of the methods used to investigate, assign and confirm the composition of the CCQM-K115/P55.2 candidate material and to demonstrate the fitness for purpose of the homogeneity, stability and reversible water adsorption/desorption of the material are given in detail in the CCQM-K115 Draft B Report [20].…”
Section: Homogeneity and Stability Studies And Sorption Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the high performance of this method, it requires a relatively large amount of peptide sample per analysis (typically 1-10 mg) [7], which generally cannot be recycled once in deuterated solvent containing the calibrant. This sample requirement is particularly detrimental when a large number of related peptide impurities are acquired that need purity assigned prior to use as quantitative standards for measuring these impurities by mass spectrometry in a peptide reference material [9][10][11]. The cost of these custom synthesized peptides can be very high, especially in the case of isotopically labelled peptides, even for quantities such as 10 mg.…”
Section: Introductionmentioning
confidence: 99%